Vehicle weight identification for a bridge with multi-T-girders based on load transverse distribution coefficient. Issue 16 (December 2019) - Zuo, Xiao-Han; He, Wen-Yu; Ren, Wei-Xin
It is still an issue to identify the vehicle weight for bridges with multi-T-girders which is essential in bridge operation management. In this study, a vehicle weight identification method is proposed for bridges with multi-T-girders. To consider the load transverse distribution effect, first the separation variable method is adopted to separate the spatial influence surface function of vehicle load into the product of two single-valued functions. Then the procedures of the vehicle weight identification method are proposed using the measured strain responses of the T-girders caused by the passing vehicle accordingly. A numerical example of a bridge with five T-girders and an experimental example of a bridge with two T-girders are conducted to verify the feasibility and effectiveness of the proposed method. Furthermore, the performance of the proposed method is compared with the typical existing method in which the load transverse distribution effect is not considered.